2020
DOI: 10.1111/btp.12794
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between local and landscape scales on the density of pond‐dwelling anurans in subtropical grasslands

Abstract: We investigated the role of local and landscape environmental variables on anurans density classified as habitat specialists and generalists in grassland landscapes, known as South Brazilian grasslands (SBG). In this region, we surveyed 187 ponds distributed over 40 landscape sampling units. For each pond, 31 local environmental variables were measured. Each landscape sampling unit was embedded within a larger regional sampling unit with different landscape properties. For each landscape and regional sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
5
1
Order By: Relevance
“…In contrast, Eterovick et al (2015) found that developmental rates and fluctuating asymmetries in the larval stage of some anurans were not explained by landscape metrics. This inconsistency of our results pinpoints a major research challenge on the effects of landscape configuration and management practices for the assemblages of anurans in the larval stage inhabiting natural savannas (Iop et al, 2020). In the present study, we showed that some species of anurans oviposit on ponds that are highly affected by the constant presence of cattle (Table 2; Supplementary Material S1).…”
Section: Relationship Between Environmental Variables Of the Habitat And The Diversity Of Anurans In The Larval Stagecontrasting
confidence: 56%
“…In contrast, Eterovick et al (2015) found that developmental rates and fluctuating asymmetries in the larval stage of some anurans were not explained by landscape metrics. This inconsistency of our results pinpoints a major research challenge on the effects of landscape configuration and management practices for the assemblages of anurans in the larval stage inhabiting natural savannas (Iop et al, 2020). In the present study, we showed that some species of anurans oviposit on ponds that are highly affected by the constant presence of cattle (Table 2; Supplementary Material S1).…”
Section: Relationship Between Environmental Variables Of the Habitat And The Diversity Of Anurans In The Larval Stagecontrasting
confidence: 56%
“…Some of these differences were expected (e.g. increase of vegetation in the pond edges, increase in water pH, loss of temporary ponds) due to agricultural practices as suppression of traditional grazing (Erős et al, 2020), relief softening (Iop et al, 2020) and application of lime for the correction of soil acidity. It is known that environmental changes may influence the relationship between host and parasite, especially for helminths with complex life cycles that require multiple hosts for transmission, development and reproduction (King et al, 2010;Koprivnikar et al, 2012a, b).…”
Section: Discussionmentioning
confidence: 99%
“…This approach was adopted because the importance of habitat descriptors can vary with spatial scale in studies on helminths and/or anuran hosts (e.g. King et al, 2007King et al, , 2010Hartson et al, 2011;Schotthoefer et al, 2011;Koprivnikar & Redfern, 2012;Iop et al, 2012Iop et al, , 2020. Thus, we were interested in identifying which of these descriptor groups better explained the quantitative descriptors of parasitism.…”
Section: Sampling Of Environmental Descriptorsmentioning
confidence: 99%
See 2 more Smart Citations